Introdução do laptop educacional em sala de aula: indícios de mudanças na organização e gestão da aula - Mendes, Mariza (2008)
The purpose of this work is accomplished an exploratory study about in progress experience in a public school located in the city of Palmas, in the state of Tocantins. This experiment is based on the project one computer per student (Project UCA), which is the introduction of an Educational Laptop in the daily life of the students, inside and outside the classroom. The objective of this exploratory study is to identify and to analyze the indications of changes that the introduction of the Educational Laptop brings to the classroom management and organization. The use of mobile and individual technology is a trend that is occurring in all the sectors in the society. In the education, there are experiments that are occurring in some parts of the world, they are searching an option for the development of a low cost equipment with connection to the Internet that can make possible the use of it by the students in any place inside and outside the school, but with a differentiated technology just for educational use. From the purpose initially collected, they had been confirmed that the presence of Educational Laptop in classroom brought alterations in the dynamics of the lesson and the teachers had needed to find new forms to manage the lesson that in such a way involves changes in the planning of the lessons as in their pedagogical practice